URGENSI MAKNA CINTA PERSPEKTIF ERICH FROMM SEBAGAI KONSEP DASAR SIKAP EMPATI KONSELOR - Ayu, Ayu Rahmawati (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
This research tries to examine the meaning of love from several important figures, such as Fahruddin Faiz who is a philosophical figure and Erich Fromm from the humanistic psychology figure and tries to relate to the concept of love in Abraham Maslow's hierarchy of needs and construct the value of love into the skills or empathy of an Islamic counselor. This research uses a qualitative approach with a library research method. The purpose of this study is that to achieve Abraham Maslow's third level of hierarchy of needs, it needs to be reviewed, namely by integrating several perspectives owned by important figures, in order to minimize the wildness of human desires in fulfilling needs and also to create human sincerity in accepting himself as a whole, taking responsibility for himself and also the object of love. So that the result of this research is the creation of a personality or high empathy attitude of a counselor by reflecting on the figure of Erich Fromm, the expert on love.